The last silk dress - Rinaldi, Ann. (New York : Bantam, 1990)
During the Civil War, Susan finds a way to help the Confederate Army and in the process uncovers a series of mysterious family secrets.
Booklist.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
8.1
8.1
7-10.
Keywords: Family problems -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; United States -- History -- 1861-1865, Civil War -- Fiction